A comparative study of acid‐treated, base‐treated, and Fenton‐like reagent‐treated biomass for Cr(VI) sequestration from aqueous solutions. (26th August 2020) - Nchoe, Obakeng B.; Ntuli, Themba D.; Klink, Michael J.; Mtunzi, Fanyana M.; Pakade, Vusumzi E.
Abstract: A wide variety of biomass materials have been used for the removal of toxic chromium(VI) by biosorption. The current study investigated the efficacy of Macadamia nutshells treated with sodium hydroxide, nitric acid, and the Fenton‐like reagent in the removal of Cr(VI). The adsorbents were characterized by FTIR, SEM, TGA, and elemental analysis. Effects of functional parameters influencing the adsorption of Cr(VI), solution pH (pH 1–11), contact time (5–250 min), concentration of adsorbent (1–10 g/L), and adsorbate concentration (10–200 mg/L) were investigated. The optimum conditions for biosorption were pH 1.4, adsorbent dose of 5 g/L, and 160 min of contact time. In all cases, the base‐treated adsorbent displayed superior performance compared to others, with highest percent removal of 98%. The adsorbate–adsorbent interactions were better explained by the Freundlich isotherm and the pseudo‐first‐order rate model. The Macadamia‐ based adsorbents are potentially useful for Cr(VI) removal from aqueous solutions. Practitioner points: Three different chemical activators were investigated for the modification of Macadamia surface. The base‐treated material exhibited the highest specific surface area of 12.1 m 2 /g. The Cr(VI) adsorption performance for the base‐treated material dwarfed the other materials. Excellent Cr(VI) removal efficiency in the presence of competitors was achieved. Abstract : A comparative study of acid‐treated, base‐treated, and Fenton‐like reagent‐treated biomass for Cr(VI) sequestration from aqueous solutions.